The large-scale whole-genome sequencing era expedited medical discovery and clinical translation - Qingxin Yang; Shuhan Duan; Yuguo Huang; Chao Liu; Mengge Wang; Guanglin He (EngMedicine)
Genomic research has been constrained by insufficient diversity over the past two decades, with over 90 ​% of studies targeting populations of European ancestry. This imbalance has hampered health equity and precision medicine, resulting in limited transferability of polygenic risk scores to underrepresented populations and misinterpretations of the pathogenicity of genomic variants. Recent advancements in sequencing technology have enabled the implementation of large-scale, high-quality, diverse, multi-omics, and engineered genomic projects, including the All of Us Research Program and the Trans-Omics for Precision Medicine Program. Coupled with the widespread adoption of electronic health records, wearable devices, and AI, the translation of these findings into clinical practice has been established for disease prediction, surveillance, and treatment across the lifespan. Here, a concise overview of the recent revolution in human genomic research is provided, emphasizing how these projects, in the era of large-scale whole-genome sequencing, have advanced genomic science, genomic medicine, and evolutionary genomics, as well as their clinical translational applications in disease prediction, cancer, drug response, and rare disease diagnosis.